(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
The experiment was carried out at Hmeimim-Jableh in Lattakia government, according to the randomized complete block design (RCBD), with three replicates per treatment during the season 2018. The research aimed to study the effect of foliar spraying with different concentrations of amino acids (0.5, 1, 2.5, 5 and 10 g/L) on some plant growth and productivity characteristics in Spanish faba bean (Vicia faba L.) (Luz de otono variety) plants. So, the morphological and physiological (plant height (cm), plant leaf area (cm2/plant), leaf area index (LAI), photosynthesis rate (g/cm2/day) and crop growth rate (g/m2/day)), the productivity (the fresh pods yield and its components and the fresh and dry seeds weight) and seed total protein content (%) have been estimated. The results showed a significant difference (P<0.05) in the response of faba bean plants to the growth and productivity under foliar application with amino acids. The plants that were sprayed with amino acids concentrations (2.5-10 g/L) revealed significantly (P<0.05) superior in most of the studied parameters. The research concluded to the importance of foliar spraying with amino acids in the studied variety, and with several concentrations higher than the recommended and used concentration. Taken together, these amino acids compounds could be recommended in foliar spraying treatments and at concentrations used in this research. نُفذ البحث في قرية حميميم (منطقة جبلة- محافظة اللاذقية)، في الموسم الزراعي 2017/2018 وفق تصميم القطاعات العشوائية الكاملة (RCBD) وبثلاثة مكررات. هدف البحث إلى دراسة تأثير الرش الورقي بتراكيز مختلفة من الأحماض الأمينية (0.5، 1، 2.5، 5 و10 غ/ل) في بعض خصائص النمو والإنتاجية والنوعية لصنف الفول الإسباني، لوز ديتونو (Luz de otono)، عبر قياس مجموعة من مؤشرات النمو المورفولوجية والفيسيولوجية (ارتفاع النبات (سم) ومساحة المسطح الورقي الكلي (سم2) ودليل المساحة الورقية (LAI)، معدل التمثيل الضوئي (غ/سم2/يوم) ومعدل نمو المحصول (غ/م2/يوم))، وعناصر الإنتاجية (غلة القرون الخضراء ومكوناتها ووزن البذور الخضراء والجافة هوائياً (غ/نبات)) ومحتوى البذور من البروتين الكلي (%). بيّنت النتائج وجود تباين معنوي (P<0.05) في استجابة نباتات الفول (لوز ديتونو) للنمو والإنتاجية تحت ظروف الرش الورقي بالأحماض الأمينية. أظهرت النتائج تفوق المعاملات التي تم رشها بالأحماض الأمينية وبتراكيز تراوحت بين 2.5-10 غ/ل معنوياً (P<0.05) في غالبية الصفات المدروسة.